Analysis of the effect of dividend policy and profitability on stock price - Wulandari, Cahya Eka; Saladin, Hendry; Mulyani, Agus (Goodwood Publishing, 2024)
Purpose: This study tests the hypothesis that dividend policy and profitability affect stock prices in food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX). Research Methodology: A quantitative approach with purposive sampling was used, selecting 15 companies (45 data points). Data were analyzed using classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). Secondary data were obtained from the official IDX reports. Results: The findings show that dividend policy and profitability significantly affect stock prices (sig = 0.000 < 0.05). Partially, dividend policy significantly affects stock prices (sig = 0.021 < 0.05), while profitability has a stronger and significant effect (sig = 0.000 < 0.05). The model explains 63% of the variation in the stock prices. Conclusions: Dividend policy and profitability are key determinants of stock price movements in the food and beverage subsector, with profitability exerting a greater influence. Limitations: This study is aimed only at Food and Beverage subsector companies listed on the IDX during the period 2020-2022. Contribution: This research is expected to be useful as a reference material in the same research and further research at PGRI University Palembang and is expected to be used as input for research sites to make decisions about the effects of dividend policy and profitability on stock prices in food and beverage subsector companies listed on the IDX.